Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/02770903.2017.1365886
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of obesity on eosinophilic vs. non-eosinophilic asthma subtypes

Abstract: Multiple clinical features of asthma are adversely affected by obesity, which may affect eosinophilic and non-eosinophilic subtypes differently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Correspondingly, the number of obese patients with asthma has also risen dramatically 15 . Obesity has been found to be a distinguishing variable for clustering and classifying asthma subtypes (e.g., enriched in women with adult onset) and the obese asthmatic is more likely to become corticosteroid resistant, has a higher risk of being hospitalized and more frequently presents with severe disease 1621 . Severe asthma is defined as asthma that requires treatment with high‐dose inhaled corticosteroids combined with a second controller and/or systemic corticosteroids to maintain control or, asthma that remains uncontrolled despite this therapy 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the number of obese patients with asthma has also risen dramatically 15 . Obesity has been found to be a distinguishing variable for clustering and classifying asthma subtypes (e.g., enriched in women with adult onset) and the obese asthmatic is more likely to become corticosteroid resistant, has a higher risk of being hospitalized and more frequently presents with severe disease 1621 . Severe asthma is defined as asthma that requires treatment with high‐dose inhaled corticosteroids combined with a second controller and/or systemic corticosteroids to maintain control or, asthma that remains uncontrolled despite this therapy 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of methodological quality was performed on the 56 articles that met the review inclusion criteria, of which nine were excluded due to poor methodological quality (online supplemental table S3). 23–31 Reference lists of included studies were hand-searched. This process identified one additional article,32 which was also assessed for eligibility and methodological quality (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies [2628] and the American Thoracic Society have concluded that obesity is a risk factor for: (1) development of de novo asthma, and (2) for complicating management in previously-diagnosed asthmatic patients [29]. The physio-pathological mechanism of this relationship is not entirely understood [30, 31] and may differ by asthma phenotypes. Nevertheless, proinflammatory effects of leptin and other obesity-related hormones may contribute to airway hyperreactivity, and, along with the restricted lung mechanics observed in obesity, these combined effects play an important role supporting the association between obesity and asthma [25].…”
Section: Discussionmentioning
confidence: 99%